PERCEIVED QUALITY PRODUK ELEKTRONIK MEREK SONY DI KOTA AMBON - Salhuteru, Andrie Ch. (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
This study aims to analyze the price factors that affect the perceived quality of Sony’s electronic products in the city of Ambon. The data of this study were collected using questionnaires distributed to consumers using Sony brand electronics products, especially audio-video category in Ambon City. The collected data was processed using SPSS 21 and then analyzed using multiple regression analysis. The result shows that the premium price variable has a positive and significant effect on perceived quality of Sony’s electronic products in Ambon City. Therefore it is recommended that the marketer always be able to pay attention to the pricing policy applied on the products it offers.